Exploring the relationship between tree defects and vandalism behaviour in Kuala Kangsar Urban Park - Hamzah, Helmi; Maruthaveeran, Sreetheran; Karlinasari, Lina; Mohd Salleh, Fariza Firdaus (Asian Scholars Network (ASNet), 2023)
The research literature describes an intimate relationship between tree defects and vandalism behaviour. Decreased growth due to mechanical injury, reduced aesthetic features from tree part loss or modification, and increased hazards related to tree part weakness are among the impacts attributed to exposure to vandalism incidents. This study aimed to identify a common explanation for these outcomes. It scrutinized the association between tree defects and vandalism behaviour. Vandalism acts were investigated at Kuala Kangsar Urban Park in Perak, Malaysia, by means of an assessment conducted on 348 trees. The survey and inventory demonstrated that the trees had six types of defects and thirteen forms of vandalism acts categorized into three different behaviour types. The results indicate that poor management and maintenance practices, as well as anthropogenic stress, significantly contribute to urban tree vandalism and defects. Decision-makers and tree managers could use the study's findings to effectively deal with the issue of vandalism towards trees in urban areas